Let
x-------> the first number
y-------> the second number
we know that
![x+y=-5 \\ x=-5-y](https://tex.z-dn.net/?f=x%2By%3D-5%20%5C%5C%20x%3D-5-y)
equation 1
![x*y=-90](https://tex.z-dn.net/?f=x%2Ay%3D-90)
equation 2
substitute the equation 1 in equation 2
![[-5-y]*y=-90 \\ -5y- y^{2} =-90 \\ y^{2} +5y-90=0](https://tex.z-dn.net/?f=%5B-5-y%5D%2Ay%3D-90%20%5C%5C%20-5y-%20y%5E%7B2%7D%20%3D-90%20%5C%5C%20y%5E%7B2%7D%20%2B5y-90%3D0)
using a graphical tool to resolve the second order equation
see the attached figure
the numbers are-12.3117.311
Answer:
90 cents
Step-by-step explanation:
23.40- 22.50= 0.90
Answer:
Step-by-step explanation:
5(p-3)
the 3 lbs she uses are being subtracted and then is being multiplied per lb
Step-by-step explanation:
हवा से भी तेज चलने वाली रोशनी है।
light travels faster than air